2019
DOI: 10.3390/plants8060151
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Tomato Plants under Saline Stress to Foliar Application of Copper Nanoparticles

Abstract: The tomato crop has great economic and nutritional importance; however, it can be adversely affected by salt stress. The objective of this research is to quantify the agronomic and biochemical responses of tomato plants developed under salt stress with the foliar application of copper nanoparticles. Four treatments were evaluated: foliar application of copper nanoparticles (250 mg L−1) with or without salt stress (50 mM NaCl), salt stress, and an absolute control. Saline stress caused severe damage to the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(73 citation statements)
references
References 68 publications
12
58
0
3
Order By: Relevance
“…Under salt stress (2000 and 4000 ppm), antioxidant enzyme activities were significantly increased in sweet pepper plants in order to combat the harmful impact of salt by adjusting osmotic balance. In agreement with our findings, similar results were noted in various plants under saline and drought conditions [68,69].…”
Section: Discussionsupporting
confidence: 93%
“…Under salt stress (2000 and 4000 ppm), antioxidant enzyme activities were significantly increased in sweet pepper plants in order to combat the harmful impact of salt by adjusting osmotic balance. In agreement with our findings, similar results were noted in various plants under saline and drought conditions [68,69].…”
Section: Discussionsupporting
confidence: 93%
“…The effect of drought stress in increasing Lipid peroxidation (MDA) and electrolyte leakage (EL) may be a result of protoplasm dehydration [39], consequently causing oxidative stress to cell membranes. The same trend was recorded under salinity stress in many plants [9,40,41]. Relative water content (RWC) significantly decreased under drought stress conditions according to the increase in plasma membrane permeability and the reduction in water supply.…”
Section: Discussionsupporting
confidence: 60%
“…Results from the ABTS method in KWS Olof ranged from 64.43 to 66.66 mg TEAC per g and from 63.76 to 65.58 mg TEAC per g. Table 4 shows that, for the antioxidant activity tested by the ABTS method, the variety and abiotic stress, like drought and intensive irradiation, have no significant influence in comparison to DPPH and FRAP methods. Differences between the antioxidant activity was also observed in study Pérez-Labrada et al [27] which observed antioxidant activity of tomato plants under abiotic stress (salinity). DPPH and ABTS behaved differently in the plants: antioxidant activity was decreased in those exposed to abiotic stress (−1.2%) while the activity by ABTS increased (4.7%).…”
Section: Antioxidant Activitysupporting
confidence: 64%